ASSESSING NOISE POLLUTION FROM MUSIC CONCERTS IN URBAN ENVIRONMENT: A CASE STUDY OF MAKASSAR CITY, INDONESIA - Muralia Hustim; Hardianti Alimuddin; Herni Halim; Muhammad Amin; Muh. Nuruzzaman Hattam (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2025)
Music concerts have increasingly raised concerns due to their contribution to noise pollution in urban environments. Aim: this study aimed to analyze noise levels and their characteristics during outdoor music concerts in Makassar City, examine the spatial distribution of noise from the source to surrounding areas, and evaluate the effectiveness of vegetation and buildings as noise barriers. Methodology and results: Observations were conducted at 16 sampling points in the Mandala Monument area and nearby urban zones. Noise mapping was carried out using the inverse distance weighting (IDW) method, and statistical analysis was performed with paired t-tests. Results indicate that even without concerts, certain urban locations exceeded the noise standards, suggesting that urbanization alone contributes significantly to noise pollution. During concerts, noise levels surpassed the Indonesian regulatory standards, with concrete structures identified as the most effective noise barriers, reducing noise intensity by up to 17.5 dB. Conclusion, Significance, and Impact Study: The findings emphasize that outdoor music concerts substantially increase environmental noise risks in urban areas. The effectiveness of structural barriers highlights their role in urban noise management. This study underscores the urgency of implementing stricter urban planning and regulatory frameworks for concerts to mitigate environmental noise and safeguard public health.